1984
DOI: 10.1080/00380768.1984.10434702
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the monosaccharide composition during the decomposition of straws under field conditions

Abstract: Changes in the monosaccharide composition during the decomposition of rice and barley straws under field conditions were examined. The proportion of mannose, galactose, fucose, rhamnose, and ribose increased consistently with time, whereas the proportion of cellulosic glucose became smaller consistently. Changes in the proportion of hemicellulosic glucose, arabinose, and xylose followed a somewhat zigzag course, though a consistent increase in the proportion of hemicellulosic glucose was observed after the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 17 publications
1
38
0
1
Order By: Relevance
“…Sugar abundances ratios, such as (Mannose + Galactose)/(Xylose + Arabinose) and (Rhamnose + Fucose)/(Xylose + Arabinose), have been used to indicate the origins, plant or microbial, of sugars in soil saccharides (Oades, 1984 ;Murayama, 1984 ). The logic is based on the types of data, referred to above [and referenced in Clapp et al (2005) ], that indicate that xylose and arabinose are largely found in plants and that mannose, galactose, rhamnose, and fucose are more likely to be found in microbial cells.…”
Section: Origins Of Soil Saccharidesmentioning
confidence: 99%
“…Sugar abundances ratios, such as (Mannose + Galactose)/(Xylose + Arabinose) and (Rhamnose + Fucose)/(Xylose + Arabinose), have been used to indicate the origins, plant or microbial, of sugars in soil saccharides (Oades, 1984 ;Murayama, 1984 ). The logic is based on the types of data, referred to above [and referenced in Clapp et al (2005) ], that indicate that xylose and arabinose are largely found in plants and that mannose, galactose, rhamnose, and fucose are more likely to be found in microbial cells.…”
Section: Origins Of Soil Saccharidesmentioning
confidence: 99%
“…According to Oades (1984), ratios of galactose + mannose to arabinose + xylose (GM/AX) <0.5 are indicative for plant-derived carbohydrates whereas those >2.0 signify a primarily microbial origin. Further, an increasing value of rhamnose + fucose to arabinose + xylose (RF/AX) reflects an increasing microbial carbohydrate synthesis (Murayama 1984).…”
Section: Analyses Of Non-cellulosic Sugars and Cuo Ligninmentioning
confidence: 99%
“…fucose)/(xylose ? arabinose) have been defined to discriminate between carbohydrates predominantly derived from plants (low ratios, \0.5) and microbial input (high ratios,[2; Murayama 1984;Oades 1984). …”
Section: Content Of Non-cellulosic Neutral Polysaccharidesmentioning
confidence: 99%